Alcohol induces neural tube defects by reducing retinoic acid signaling and promoting neural plate expansion - Edri, Tamir; Cohen, Dor; Shabtai, Yehuda; Fainsod, Abraham (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Neural tube defects (NTDs) are among the most debilitating and common developmental defects in humans. The induction of NTDs has been attributed to abnormal folic acid (vitamin B9) metabolism, Wnt and BMP signaling, excess retinoic acid (RA), dietary components, environmental factors, and many others. In the present study we show that reduced RA signaling, including alcohol exposure, induces NTDs. Methods:Xenopus embryos were exposed to pharmacological RA biosynthesis inhibitors to study the induction of NTDs. Embryos were treated with DEAB, citral, or ethanol, all of which inhibit the biosynthesis of RA, or injected to overexpress Cyp26a1 to reduce RA. NTD induction was studied using neural plate and notochord markers together with morphological analysis. Expression of the neuroectodermal regulatory network and cell proliferation were analyzed to understand the morphological malformations of the neural plate. Results: Reducing RA signaling levels using retinaldehyde dehydrogenase inhibitors (ethanol, DEAB, and citral) or Cyp26a1-driven degradation efficiently induce NTDs. These NTDs can be rescued by providing precursors of RA. We mapped this RA requirement to early gastrula stages during the induction of neural plate precursors. This reduced RA signaling results in abnormal expression of neural network genes, including the neural plate stem cell maintenance genes, geminin, and foxd4l1.1. This abnormal expression of neural network genes results in increased proliferation of neural precursors giving rise to an expanded neural plate. Conclusion: We show that RA signaling is required for neural tube closure during embryogenesis. RA signaling plays a very early role in the regulation of proliferation and differentiation of the neural plate soon after the induction of neural progenitors during gastrulation. RA signaling disruption leads to the induction of NTDs through the mis regulation of the early neuroectodermal network, leading to increased proliferation resulting in the expansion of the neural plate. Ethanol exposure induces NTDs through this mechanism involving reduced RA levels.